Business Plan Proposal Preparation Training for Tsanawiyah Madrasah Students - Hugo Aries Suprapto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This activity aims to provide knowledge to students about the importance of making business plan proposals to improve entrepreneurship skills. The output target of this activity is that it is hoped that students will find it easier and more understandable in understanding proposal writing by cultivating creative and innovative ideas and increasing interest in entrepreneurship. The activity method is carried out in two stages, the first stage is direct observation and demonstration and counseling. The number of participants was 45 class X students. Teaching will be conducted 4 face to face so that Mts Nurul Hikmah students have a better understanding of making business plan proposals. The results of the activity show that students have been able to compile business proposals both in theory and practice with a pretty good category. Activities can be developed with other themes such as how to market products effectively for students.